An Assessment of the Business Innovation Model Strategy used to enhance information technology by ABSA - Sidali, Nozi (University of the Witswatersrand, Johannesburg, 2022)
The purpose of this research was to provide an analysis and understanding of how ABSA bank dealt with inertia, resistance to change and managed to have a low risk tolerance during the implementation and adoption of their revised business model where transformation attempts sometimes do not achieve the expected objectives. For this astudy, the researcher used ABSA bank’s Information Technology Strategy with the requirements and characteristics of a business model innovation and outlined the primary innovation enablers that assisted the bank becoming a digitally powered business amongst its competitors in South Africa (SA). In South Africa, the topic of innovation, digitalisation and digitising banks has always been an ever-present agenda item for the banking sector. However, before the recent Covid -19 pandemic, these topics were still in their infancy in most banks. They have challenged the traditional old-age business models within many organisations. This study will assess ABSA bank’s Information Technology Strategy as a business model, relate it to the industry- used business models, determine if it complies with the requirements and characteristics of a business model innovation, and determine to what extent the relationship is. Listed on the JSE, ABSA is a proudly pan-African bank with a geographical footprint in 13 countries such as (Botswana, Ghana, Kenya, Mauritius, Mozambique, Seychelles, South Africa, Tanzania, Uganda, and Zambia) and prides themselves on diversity, also having entities in the United Kingdom, the United States as well an IT specialist office in the Czech Republic (ABSA, 2022). For this study, the researcher applied a intepretivism research paradigm to analyse and understand ABSA’s information technology strategy and business model, the itertia and how the bank managed to have a low risk tolerance during its implementation and adotion. A random sampling method was used to select the twelve participants to collect data for this study and ensure a fair diversity regarding ethnicity, job roles, job grade, gender and employee tenure within ABSA. A highlight from the findings of this research suggests with no doubt, ix digital transformation, the importance of innovating a business model and its benefits are a vehicle that could assist organisations to stand out from their competitors, gain more revenue and upscale. The analysis of this ABSA case and benchmarking the researcher did during this study states that it takes a few iterations of innovation before successfully innovating a business model for any organisation. When done right, this research suggests that innovating business models for organisations can be the most powerful tool for any business
A research proposal submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Management in the field of Digital Business
Keywords: ABSA bank; Business mode; Information Technology Strategy; Innovation; Covid -19 pandemic; SDG-8: Decent work and economic growth